The Influence of Digital Literacy of Small Business Actors on The Level of E-Commerce Use in Blitar District - Siti Azizah; Arifatus Sholikhah; Irfan H. Djunaidi; Diah Priharsari; Mas Ayu Ambayoen; Siti Hamidah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
MSME entrepreneurs assisted by the Livestock and Fisheries Service in Blitar Regency are classified as independent MSMEs on a household scale, so it is necessary to market e-commerce to achieve a national economy that can improve the welfare of business actors and the community. This research was conducted on MSME business actors assisted by the Livestock and Fisheries Service from several OPS MSME members, PPMK Srikandi, AKBest product business actors, and mothers of "MuZa" smoked salted egg product business spread across Blitar Regency. The time to research for This study uses a quantitative method with a methodological approach in the form of a survey. The results of the study indicate that the characteristics of MSME business actors assisted by the Livestock and v Fisheries Service in Blitar Regency, most of the business actors obtain capital sources from privately owned funds, with a monthly income of Rp. 3.082.105 ± Rp. 4.941.308, and the duration of the business is 1-5 years, while the business model is still classified in the category of independent MSMEs